Edukasi dan Pengembangan Keterampilan Menggambar Kartun Anime untuk Melatih Kecerdasan Anak-anak di Panti Asuhan Amanda Kota Palangka Raya - Amiany, Amiany; Widati, Titiani; Virgiyanti, Lisa; Sirenden, Ruben Tinting (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Art is useful for developing skills in children, because art fosters creativity in children. Creativity is an experience in expressing and actualizing individual identity that integrated  between relationships with oneself, nature, and others. Palangka Raya is considered to have the potential to be developed as one of the centers for the development of arts and cultural activities in the Central Kalimantan Province. Based on observations, the obstacle in carrying out the activities of the PDPSU is that there is no information for ordinary people  to learn the skill of drawing anime cartoons, while many elementary age children like to watch cartoons. From these shows, the majority of Panti Asuhan Amanda are interested in drawing anime cartoons. The inability of the group of children at the Panti Asuhan Amanda in Bukit Tunggal Village to draw anime cartoons is because they do not have knowledges of these skills. Based on the above problems, the PDPSU LPPM Team of Palangka Raya University supports by providing education related to skills. drawing anime cartoons. Education and skill development activities include: (1) preparation, observation; (2) location survey and coordination; (3) socialization and mentoring stages; and (4) evaluation stages. The results obtained from skill education in drawing anime cartoons are increased ability of Panti Asuhan Amanda’s children in drawing anime cartoons. It is hoped that this drawing skills education can develop fine motor skills, develop children's imagination, creativity and initiative and train children at Panti Asuhan Aamnda  to be able to express themselves and ideas more freely.